2015
DOI: 10.1212/wnl.0000000000001891
|View full text |Cite
|
Sign up to set email alerts
|

The unruptured intracranial aneurysm treatment score

Abstract: Objective:We endeavored to develop an unruptured intracranial aneurysm (UIA) treatment score (UIATS) model that includes and quantifies key factors involved in clinical decision-making in the management of UIAs and to assess agreement for this model among specialists in UIA management and research.Methods:An international multidisciplinary (neurosurgery, neuroradiology, neurology, clinical epidemiology) group of 69 specialists was convened to develop and validate the UIATS model using a Delphi consensus. For i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
187
3
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 345 publications
(196 citation statements)
references
References 29 publications
1
187
3
5
Order By: Relevance
“…19 In practice, other potential causes have to be searched for and treated, whereas the unruptured aneurysm can be managed according to current guidelines. 20 The opponents suggested that catheter angiography was not necessary after normal CT and LP, because these patients had "benign TCH." This suggestion was based on two prospective studies of patients with sudden headaches, who were all investigated by brain CT without contrast and LP after normal CT, but who had no catheter angiography after normal CT and LP.…”
Section: History Of the Recognition Of Rcvs As A Common Cause Of Tchmentioning
confidence: 99%
“…19 In practice, other potential causes have to be searched for and treated, whereas the unruptured aneurysm can be managed according to current guidelines. 20 The opponents suggested that catheter angiography was not necessary after normal CT and LP, because these patients had "benign TCH." This suggestion was based on two prospective studies of patients with sudden headaches, who were all investigated by brain CT without contrast and LP after normal CT, but who had no catheter angiography after normal CT and LP.…”
Section: History Of the Recognition Of Rcvs As A Common Cause Of Tchmentioning
confidence: 99%
“…8 Risk scores combining multiple risk factors to predict the rupture of unruptured sIAs have been developed, such as Population, Hypertension, Age, Size of sIA, Earlier SAH From Another sIA, Site of sIA (PHASES) 17 and the Unruptured Intracranial Aneurysm Treatment Score (UIATS). 18 To determine the usefulness of size and irregular sIA shape as markers of an unstable rupture-prone sIA wall at different locations and in different patient subpopulations, we studied an unselected consecutive series of ruptured and unruptured saccular nonmycotic aneurysms diagnosed and treated 1980 to 2014 in the Kuopio University Hospital (KUH). We focused especially on those sIAs that eventually ruptured, and on how well size or shape would have identified those sIAs as rupture prone and thus necessitating treatment.…”
Section: May 2016mentioning
confidence: 99%
“…Even if these tests are easily applicable and correlate well with the severity of the disease, they have numerous limitations and thus need more validation. [6][7][8][9] For instance, aneurysm size remains a major criterion for treatment as it is assumed that large IAs are at higher risk for rupture than small IAs. However, small IAs with regular shape may also rupture.…”
Section: Introductionmentioning
confidence: 99%